2015
DOI: 10.1111/jcal.12097
|View full text |Cite
|
Sign up to set email alerts
|

Inventing motivates and prepares student teachers for computer‐based learning

Abstract: A brief, problem-oriented phase such as an inventing activity is one potential instructional method for preparing learners not only cognitively but also motivationally for learning. Student teachers often need to overcome motivational barriers in order to use computer-based learning opportunities. In a preliminary experiment, we found that student teachers who were given paper-based course material spent more time on follow-up coursework than teachers who were given a well-developed computer-based learning env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 77 publications
(130 reference statements)
0
9
0
Order By: Relevance
“…With various studies exploring differences in paper‐ and computer‐based resources (Lee and Weerakoon, ; Maleck et al, ; Chang et al, ; Cantillon et al, ; Glogger‐Frey et al, ; Poulton et al, ; Shotwell and Apigian, ), and student perceptions not necessarily being overwhelmingly positive (Berg et al, ; McNeish et al, ), it is important to understand how the design of multimedia resources can support the learner (Wilson, ). By comparing the anatomy drawing screencast to the textbook in relation to the principles of the CTML, it could be postulated that the differences in learning gain are due to this instructional design approach with obvious differences being drawn.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With various studies exploring differences in paper‐ and computer‐based resources (Lee and Weerakoon, ; Maleck et al, ; Chang et al, ; Cantillon et al, ; Glogger‐Frey et al, ; Poulton et al, ; Shotwell and Apigian, ), and student perceptions not necessarily being overwhelmingly positive (Berg et al, ; McNeish et al, ), it is important to understand how the design of multimedia resources can support the learner (Wilson, ). By comparing the anatomy drawing screencast to the textbook in relation to the principles of the CTML, it could be postulated that the differences in learning gain are due to this instructional design approach with obvious differences being drawn.…”
Section: Discussionmentioning
confidence: 99%
“…This study aims to continue investigating the integration of anatomy drawing screencasts into a medical anatomy curriculum by comparing the learning gain achieved to a traditional paper‐based resource. Numerous studies have assessed the impact of digitally delivering resources compared to a paper‐based equivalent for assessment (Lee and Weerakoon, ; Cantillon et al, ; Shotwell and Apigian, ), case‐based teaching (Maleck et al, ; Poulton et al, ), motivation (Glogger‐Frey et al, ) and patient outcomes (Chang et al, ) with contrasting results. Although it is appreciated that web‐based learning is effective, issues such as information technology (IT) experience, independent study skills and password accessibility need to be addressed prior to implementation (Wilkinson et al, ; Cook et al, ; Cook, ).…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study (Glogger-Frey et al, 2015), we found that an inventing group indeed outperformed a control group. The control group had read a text which was designed to givedas much as possibledthe same information as the inventing group got or generated, respectively.…”
Section: How Can Motivational Processes Explain the Present Effects?mentioning
confidence: 92%
“…To conceptualize the pretraining intervention, we first needed to identify activity categories that (preservice) teachers often confuse with learning strategies. Therefore we reanalyzed pretest data from previous studies (Glogger, Kappich, Schwonke, Holzäpfel, Nückles, & Renkl, 2011; Glogger et al., 2012) originally used to control for differences in prior knowledge. Furthermore, we considered findings from studies in the USA (Clift et al., 1990; Hamman, 1998) that analyzed teachers' knowledge about learning strategies.…”
Section: Methodsmentioning
confidence: 99%